2014
DOI: 10.1080/15599612.2014.901455
|View full text |Cite
|
Sign up to set email alerts
|

Optical Property Analyses of Plant Cells for Adaptive Optics Microscopy

Abstract: In astronomy, adaptive optics (AO) can be used to cancel aberrations caused by atmospheric turbulence and to perform diffraction-limited observation of astronomical objects from the ground. AO can also be applied to microscopy, to cancel aberrations caused by cellular structures and to perform high-resolution live imaging. As a step toward the application of AO to microscopy, here we analyzed the optical properties of plant cells. We used leaves of the moss Physcomitrella patens, which have a single layer of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Alternatively, spectral unmixing can be used to separate each contribution [34]. Furthermore, chloroplasts, mitochondria, starch granules and the cell wall are all light-scattering structures [35][36][37]. Collectively, background light absorbing, emitting and scattering factors reduce both excitation and signal detection efficiencies in whole-mount fresh tissues.…”
Section: Important Considerations Prior To Imagingmentioning
confidence: 99%
“…Alternatively, spectral unmixing can be used to separate each contribution [34]. Furthermore, chloroplasts, mitochondria, starch granules and the cell wall are all light-scattering structures [35][36][37]. Collectively, background light absorbing, emitting and scattering factors reduce both excitation and signal detection efficiencies in whole-mount fresh tissues.…”
Section: Important Considerations Prior To Imagingmentioning
confidence: 99%
“…The value D∕r 0 denotes the number of turbulent cells aligning on the aperture diameter, frequently used to indicate the degree of image degradation. The residual wavefront error after AO correction was σ AO ¼ 0.16 rad, theoretically yielding a Strehl ratio, r ST ¼ expð−σ 2 AO Þ of 0.98. 5 This is the same level reported by Tao et al 7 However, Strehl ratios measured from the observed images ought to be lower than those derived from residual phase errors on the sensor.…”
Section: Defocus Aberrationmentioning
confidence: 99%
“…Parts of the foggy components may have arisen from the diffusion of light occurring on the etched surface of the coverslip, where about half the wavelength of depth enhanced the diffractive errors. 2,17 Figures 7(g)-7(i) show the AO-corrected images. As expected, bead images of 1.0-μm diameter around the reference patterns became finer such that their individual shapes were distinguishable as being spherical.…”
Section: Higher-order Aberrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that PSAs with higher numbers of images tend to be more robust against phase unwrapping failures which may arise due to combinations of modulation between reference and object beams, and mechanical vibrations. The literature indicates typical refractive indices of the cell wall (n = 1.41−1.52) for flowering plants, 28 cytoplasm (n = 1.36 − 1.39), nucleus (n = 1.355 − 1.65) and nucleolus (n = 1.375 − 1.385) for animal cells. 29,30 These values are numerically consistent; however, it should be noted that the uncertainty in refractive index limits the ability to accurately quantify the thickness of organelles in many cases; additionally, preparation of the sample between microscope slides may also affect the thicknesses measured.…”
Section: Phase Measurement From a Biological Samplementioning
confidence: 99%